THE INFLUENCE OF LIFESTYLE AND METABOLIC SYNDROME ON BREAST CANCER INCIDENCE AND PROGNOSIS (Global Conference on Medical and Health Sciences, 2026)
Breast cancer incidence continues to rise globally, partly due to lifestyle transitions and increasing prevalence of metabolic disorders. Metabolic syndrome—a cluster of conditions including central obesity, insulin resistance, dyslipidemia, and hypertension—has been increasingly recognized as a significant contributor to breast cancer development and progression. Lifestyle factors such as sedentary behavior, high-calorie diets, excessive body weight, and reduced physical activity influence hormonal balance, chronic inflammation, and metabolic dysregulation, thereby promoting carcinogenesis.
Keywords: Breast cancer; lifestyle factors; metabolic syndrome; obesity; insulin resistance; inflammation; prognosis; prevention; public health; cancer epidemiology.